(3GdLRA ef GdaGJMI CjVG aj QSGFd GdTgjO GdKGfj h GdQSGFd GdQLGdjI dCHj GdeYGdj GdcdjHGSjs - (3eLghds
(3ChdgG (B:s
.. (3abO PcQ GdcTj aj cJGHg GdebHhd hZjQg Hd hPcQg HgPg GdMGdI LejY GdeUfajf hef gh CLd ef GdcTj de jaO Pdc bHhdg acja HeKd GdcTj (B...s
(3BNQgG (B:s
... (3hUGMH GdQSGdI GdJj CTQfG ajeG JbOe Edi (B.. (3hbO GSJhajfG (B.. (3GdCHMGK hGdcdGe aj GdQSGdI GdJj cJHfG aj GdQO Ydi GdQSGdI GdePchQI (B.. (3Jes
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
(3Qbej ZjQ edhfs
(3ehGUaGJ GdfSNI (B: s
(3ceGd GdfSNI (B:s
Keywords: (3GdJhMjO hGdedd hGdfMds